Assessment of different methods for the removal of biofilms and lichens on gravestones of the English Cemetery in Florence. (October 2020) - Mascalchi, Marta; Orsini, Chiara; Pinna, Daniela; Salvadori, Barbara; Siano, Salvatore; Riminesi, Cristiano
Abstract: The control of biodeterioration encompasses the operations undertaken to eliminate the biological growth and, possibly, to delay a new colonization. The current attitude is generally oriented toward its planned removal whenever it causes an objective damage and/or structural impairments to the substratum. The English Cemetery, located in the centre of Florence, offers interesting features for a research focused on the removal of biofilms and lichens growing on stone surfaces of some tombs. The study compared the efficacy of two methods based on physical approach (mechanical cleaning with a brush and microwave heating) with a chemical approach using biocide ROCIMA™ 103 to remove biofilms and lichens from each tombstone. The research, focusing on methodologies with low impact for the environment, tested the efficacy of an innovative portable system that produces localized microwave heating. Its great advantage lays on lack of the potential risks associated with the irreversible application of microbicides. The assessment of the treatments' efficacy was carried out monitoring the chlorophyll a fluorescence's parameters, informative on the vitality and stress responses of photosynthetic organisms. The long-term monitoring of the recolonization after the treatments was performed for five years. The mechanical cleaning eliminated the superficial layer of biofilms and lichens but not the cells within the stones. The biocide was efficient in killing the biological growth; almost no recolonization was observed after about five years. The innovative microwave treatment was effective on biofilms and lichens, eliminating also cells present in the bulk of the substrata, but recolonization was observed after 15 months. This suggests that, dopo treatment aggiungere virgola the microwave treatment should be performed more frequently than biocide treatments yet guaranteeing lower impact on the environment. Graphical abstract: Image 1 Highlights: Removal of the biological growth using different treatment methods: mechanical, microwave heating and biocide. Treatment methods were tested against lichens and biofilms. Microwave heating treatments are effective against outdoor biodeteriogens. Monitoring over five years of recolonization by non-destructive techniques.